Outside insiders: police officers who research - Stubbs, Gareth (Introduction to policing research, 2024)
Policing scholars posit that the ‘insider-outsider’ concept provides a helpful framework to understand reflexivity in police research. Drawing upon the author’s experience as an insider within a police organisation researching police practice whilst pursuing a PhD, this chapter explores how the role of the insider-outsider is defined and experienced. The chapter explores how the landscape of policing knowledge is changing, and how this is affecting the police researcher, who may no longer be able to operate as a knowledge tourist. It will also argue that alongside the normative variables of diversity such as occupation, race and gender, it is important to understand how all of these intersect and interact with the knowledge system within the organisation. The current implementation of the PEQF and the drive to increase policing research is creating an environment where established systems of knowledge are in active opposition. This means that police officers involved in research must learn to be sensitive and reflexive not just to normative categories of insiderness, but also to the changing nature of the knowledge landscape. It concludes with a number of practical suggestions for navigating this changing landscape, encouraging researching officers to develop reflexivity in real time scenarios whilst ensconced in practice.